Bacterial Detection and Anatomical Descriptions of the DigestiveSystem of the Iraqi Gecko (Hemidactylus turcicus) in BaghdadProvince - Kallo, Osama; Hussin, Amer (Iraqi Journal of Science, 2025)
This study was carried on 64 Geckos of different sizes collected from fivelocations at Baghdad province over a period from July 2002 up to February 2003.Bacteriological examination of 84 swabs taken from the digestive tract of theseanimals revealed that 81 swabs (96.4%) were positive for bacterial isolates. The mostpredominant bacteria were Salmonella spp. (50%) followed by E.coli (26.2%) andKlesiella spp. (14.3%), which were isolated mostly from the small intestine andfeces. The highest frequency of Salmonella infection was observed in Geckoscollected from Al-Mahmodeia and Al-Amereia (100%), (83%) respectively, whereas the lowest frequency (26.6%) was found in Geckos collected from Baghdad Al-Jadida. Geckos of large size were more frequently infected in comparison with thesmaller size. However the study of the anatomy of the digestive system showed thatGeckos have a wide triangular mouth with pointed teeth, the stomach was small andthe duodenum was large, the liver had a gall bladder and the pancreas opens in to theduodenum by many ducts. The study indicated that the large size of the duodenumplays an important role in bacterial growth and multiplication. Therefore it could beconcluded that Geckos considered to be a source and reservoir for harmful pathogensthat could be transmitted to human beings.